Regional Differences of Manufacturing Green Development Efficiency Considering Undesirable Outputs in the Yangtze River Economic Belt Based on Super-SBM and WSR System Methodology - Li, Gen; Zhou, Ying; Liu, Fan; Wang, Tao (Frontiers in Environmental Science, 2021)
Based on the panel data of 11 provinces and cities in China's Yangtze river economic belt from 1998 to 2017, the super-SBM model is used to calculate the efficiency of green development. The innovation of this paper is to fully consider the resource input and undesired output in the production process. Then, the regional differences in green development efficiency of manufacturing industry in the Yangtze economic belt are deeply analyzed, then, using the WSR methodology to construct the index system of influencing factors, finally, Tobit model is used to analyze the factors influencing the green development efficiency of manufacturing industry in the Yangtze economic belt. And it turns out, during the statistics period, manufacturing green development in the Yangtze river economic belt is "U" type of efficiency, the average value of each province over the years is 0.812, at the medium level of development; the green development efficiency of manufacturing industry in the Yangtze river economic belt is on the rise, and the low scale efficiency is the main reason that restricts the green development efficiency of the Yangtze river economic belt. All the influencing factors have different effects on the green development efficiency of manufacturing industry in different regions. Therefore, this paper puts forward corresponding policy suggestions from the three dimensions of Wuli, Shili and Renli theory.